Vascular niches for disseminated tumour cells in bone - Anjali P. Kusumbe (Journal of Bone Oncology, 2016)
The vasculature of the skeletal system regulates osteogenesis and hematopoiesis, in addition to its primary function as a transportation network. Recent studies suggest that the vasculature in bone regulates multiple steps involved in the metastatic cascade. Matrix and growth factor abundant vascular microenvironments in bone not only provide a fertile soil for the metastatic growth but also support the dormancy of Disseminated Tumour Cells (DTCs). Interestingly, vasculature also seems to direct the reactivation of dormant DTCs. Targeting such early steps of bone metastasis by directing therapies against vascular niches can lead to the development of effective therapeutic strategies that delay or even prevent the metastatic relapse. However, this would require a detailed understanding of the regulatory mechanisms that govern the interaction between endothelial cells and DTCs in the early stages of bone metastasis. This review aims to highlight the importance of vascular niches and outline their newly identified roles during bone metastasis.